1987
DOI: 10.1159/000184571
|View full text |Cite
|
Sign up to set email alerts
|

Taste Sensitivity for Sodium Chloride in Hypotensive, Normotensive and Hypertensive Subjects

Abstract: The taste sensitivity for sodium chloride was examined in 103 normotensive, 55 hypertensive and 36 hypotensive subjects. The examination was performed on five areas of the tongue using four different concentrated NaCl solutions (2.5, 5,0, 7.5 and 15%). The results indicate that hypotensive subjects show a much higher salt sensitivity compared to normotensive or hypertensive subjects. The enhanced sensitivity of hypotensives to sodium chloride may reflect a regulatory factor tending to normalize blood pressure.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 8 publications
1
9
1
Order By: Relevance
“…Although some early studies performed in Western populations suggested a relationship between salt taste and blood pressure, the studies were performed in clinical settings and did not show the results stratified by sex. 15,16,[26][27][28] Therefore, it is difficult to compare those results with the results of our study. Because this was a cross-sectional study, prospective studies regarding the connection between the taste of salt and blood pressure are needed.…”
Section: Discussionmentioning
confidence: 60%
“…Although some early studies performed in Western populations suggested a relationship between salt taste and blood pressure, the studies were performed in clinical settings and did not show the results stratified by sex. 15,16,[26][27][28] Therefore, it is difficult to compare those results with the results of our study. Because this was a cross-sectional study, prospective studies regarding the connection between the taste of salt and blood pressure are needed.…”
Section: Discussionmentioning
confidence: 60%
“…Some of them revealed a positive correlation between salt perception and blood pressure while others did not (7,8).…”
Section: J Arguelles Et Almentioning
confidence: 99%
“…Because of the well-established link between high dietary salt intake and blood pressure 2 , salty taste has long been an area of focus in examining differences between hypertensives and normotensives in terms of hedonic appeal of salt 3–5 , perceived salty taste intensity 6,7 , and sensitivity to salty taste 5,8–14 , as any differences between these groups may allow for diagnosing or managing hypertension 7,15 . To date, findings from research of this nature have been largely equivocal.…”
Section: Introductionmentioning
confidence: 99%
“…No definitive association between blood pressure and either salt preference 3–5 or perceived salty taste intensity 6,7 has been published thus far. Examinations of the link between blood pressure and salty taste sensitivity, measured via detection thresholds (defined as the lowest concentration of a stimulus needed by a subject to detect its presence relative to water 16 ) or recognition thresholds (defined as the lowest concentration of a stimulus correctly identified by name by a subject based on its characteristic taste 16 ), have produced mixed results.…”
Section: Introductionmentioning
confidence: 99%